SERS spectra of a single nasopharyngeal carcinoma cell based on intracellularly grown and passive uptake Au nanoparticles. Issue 3 (2011) - Huang Huang, Hao Hao; Chen Chen, Weiwei Weiwei; Pan Pan, Jianji Jianji; Chen Chen, Qisong Qisong; Feng Feng, Shangyuan Shangyuan; Yu Yu, Yun Yun; Chen Chen, Yanping Yanping; Su Su, Ying Ying; Chen Chen, Rong Rong
Abstract : The intracellularly-grown-Au-nanoparticles (IGAuNs) technique was employed to analyze the surface-enhanced Raman scattering (SERS) spectra of nasopharyngeal carcinoma cells (CNE-1 cell line). There are only six obvious Raman bands (718, 1001, 1123, 1336, 1446, 1660 cm −1 ) in the normal Raman spectrum of living CNE-1 cells. However, over twenty SERS Raman bands have been detected in the SERS spectra of IGAuNs-induced cells, among which five bands are of the DNA backbone (673, 1097, 1306, 1336 and 1585 cm −1 ). There are four vibrations of the DNA backbone (1026, 1097, 1336 and 1585 cm −1 ) in the SERS spectra of living CNE-1 cells induced by the passive uptake gold nanoparticles (PUAuNS), but one more DNA backbone and many nucleus Raman peaks appeared in the IGAuNs-induced SERS spectra. Many Raman peaks in the PUAuNs-induced SERS spectra are stronger than those in the IGAuNs-induced ones. This study has shown that the PUAuNs technique can achieve stronger Raman signals, and that the IGAuNs technique can enable the gold element to access to the nucleus more easily, which could help to obtain more surface-enhanced Raman signals of the intracellular biochemical molecules. Thus, the two techniques can work together to attain the Raman spectral information of the cytoplasm and the nucleus in a better way, which might provide a sensitive method for broad biomedical applications such as intracellular SERS analysis of living cells.